(untitled) (Psychology Travelogs, 2022)
The article reveals the essence of the psychological features of professional stress of the specialists of socionomic profile. The necessity of psychological features of professional stress on whom efficiency of introduction of professional activity of the specialists of socionomic profile. The essence of concepts is specified: stress, stressors, professional stress, professional stress of the specialists of socionomic profile, information stress, communication stress, emotional stress, eustress, distress, acute (short) stress, chronic stress, stress resistance. The study of the psychology of professional stress, ways and methods of its correction and prevention is important for specialists of socionomic profile in a number of life and professional events. The problem of professional stress of the specialists of socionomic profile due to the fact that the work performed does not always correspond to the required level of their psychological readiness to withstand intellectual stress. In the process of professional activity, specialists of socionomic profile are systematically exposed to psycho-emotional influences associated with excessive demands, a high level of control over situations and limited resources for the possibility of their change and improvement. It is very important for specialists of socionomic profile to learn not only to perform professional tasks, but also to learn to regulate their psycho-emotional state. That is why the psychology of professional stress in the field of man-to-man needs more detailed study. The results of an empirical study of stress resistance and assessment of adaptive resources of the specialists of socionomic profile. According to the results of the study, it is determined that the vast majority of specialists of socionomic profile have an average of stress resistance. We see the prospect of further research in the development and implementation of a psycho-correctional program that will promote the development of resilience to stressful situations and maintaining the mental health of the specialists of socionomic profile.